The Urgency of Sighat Takliq Talaq as a Protective Measure Law for Wives - Syifa Rahmi Utami; Mar Fajar Rizkyansyah; Mochamad Syafiudi (Zona Law And Public Administration Indonesia, 2023)
Taklik talaq is a marriage agreement pronounced by the bridegroom after the procession of the marriage contract listed in the marriage book in the form of talaq promises that depend on a certain situation. Sighat taklik talaq aims to protect the rights of wives from the arbitrariness of husbands. Based on the reality on the ground, not all couples take the sighat taklik talaq after the marriage contract. This happens because of the lack of socialization about taklik talaq, causing there are still many married couples who do not understand the purpose of the sighat taklik talaq itself. The research method used is a descriptive method of analysis, Based on the research conducted, researchers found several findings, namely With the existence of talaq wife gets a guarantee of legal protection in marital relationships. Although the legal basis of talaq in marriage itself is mubah, it can guarantee legal certainty for the wife in marriage. Taklik talaq provides legal protection in the form of the right to file a divorce lawsuit if the husband leaves his wife for two consecutive years, legal protection for the wife when the husband does not provide compulsory income for three months, Protection of the wife from the husband who hurts the wife physically/spiritually, Protection of the wife whose husband abandons the wife for six months